Gender Diversity dan Independensi Dewan Pengawas: Dampaknya Terhadap Kinerja Pasar Bank Syariah di Indonesia - Frihatni, Andi Ayu; Hamid, Abdul; Mardatillah, Hasfriani (AKTSAR: Jurnal Akuntansi Syariah, 2025)
This study aims to analyze the effect of gender diversity and the independence of the Sharia Supervisory Board (SSB) on the market performance of Islamic banks in Indonesia. The background of this study is based on the limited empirical studies that assess the role of gender diversity and DPS independence in the context of market-oriented Islamic banking governance. The research method uses a quantitative approach with panel data regression analysis based on the Random Effect Model (REM). Data were obtained from financial reports and publications of Islamic banks during the 2014–2024 period. The result show that gender diversity has a positive and significant effect on market performance. In contrast, the SSB independence variable (X₂) shows a coefficient of 0.0017, a probability value of 0.4176 (p > 0.05), and a t-statistic of 0.8135, indicating an insignificant statistical effect on market performance. Simultaneously, the F-test result shows that the regression model is significant at the 95% confidence level with an F-statistic of 5.9217 and Prob(F-statistic) = 0.0035. The Adjusted R² value of 0.0758 indicates that the independent variables jointly explain 7.58% of the variation in the market performance of Islamic banks, while 92.42% is explained by other factors outside the model. These findings confirm that gender diversity within the SSB contributes to enhancing market confidence and perception toward Islamic banks’ performance, whereas SSB independence has yet to demonstrate a significant role in influencing market-based performance.